Social Banking and Social Finance Answers to the Economic Crisis - Benedikter, Roland; SpringerLink (Online service)0. (New York, NY Springer New York Imprint: Springer, 2011)
For over 2,000 years, banks have served to facilitate the exchange of money and to provide a variety of economic and financial services. During the most recent financial collapse and subsequent recession, beginning in 2008, banks have been vilified as perpetrators of the crisis, the public distrust compounded by massive public bailouts. Nevertheless, another form of banking has also emerged, with a focus on promoting economic sustainability, investing in community, providing opportunity for the disadvantaged, and supporting social, environmental, and ethical agendas. Social Banking and Social Finance traces the emergence of the ?bank with a conscience? and proposes a new approach to banking in the wake of the economic crisis. Featuring innovations and initiatives in banking from Europe, Canada, and the United States, Roland Benedikter presents an alternative to traditional banking practices that are focused exclusively on profit maximization. He argues that social banking is not about changing the system, but about improving some of its core features by putting into use the "triple bottom line" principle of profit-people-planet. Important lessons can be learned by the success of social banks that may be useful for the greater task of improving the global financial system and avoiding economic crises in the future.
The Financial and Economic Crisis of 2007 2010: A View from the Standpoint of Social Banking and Social Finance -- Origins and Causes of the Crisis: The Sandglass Principle of the Mainstream Banking and Finance System Between 1989 and 2007 -- Social Banking and Social Finance: New Approaches to Money and Finance -- What Is a Social Bank Definitions and Practices -- What Is Money and What Is Capital According to Social Banking The Concept of Liberation Finance -- What Is the Philosophy of a Social Bank -- Where Do Social Banks Come From A Very Short History -- The State of Social Banking and Social Finance Today: A Brief Comparison Between the United States and Europe -- Seven Answers to the Financial Crisis -- The More Important Challenge: Getting a Balanced and Integrative Viewpoint on Money and Finance -- Ideas for a New Financial Humanism: The Interweaving of Three Core Solutions to the Financial and Economic Crisis in Order to Build a Better Future -- Conclusion and Outlook -- Epilogue: Toward a Financepeace The Integrative Mindset of Social Banking and Social Finance and Its Critics
Electronic reproduction.
Keywords: Banks and banking -- Moral and ethical aspects; Finance -- Moral and ethical aspects; Global Financial Crisis, 2008-2009.; Social responsibility of business; Social capital (Sociology) -- Economic aspects